Pengaruh Influencer Marketing, WOM(Word Of Mouth) Dan Brand Image Terhadap Keputusan Pembelian Di Chatting Café & Dimsum Di Kota Pontianak - Ernawati, Reni; Aisyah; Dewi Rawa, Ricola; Febrianawati (Prodi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Panca Bhakti, 2025)
This study aims to determine the influence of influencer marketing, word of mouth (WOM), and brand image on purchasing decisions at chatting cafes and dimsum in Pontianak City. This study used a quantitative approach and multiple linear regression analysis using SPSS version 26 software. The sampling technique used accidental sampling with a non-probability sampling method, with a sample size of 170 respondents. The results showed that simultaneously, influencer marketing, word of mouth (WOM), and brand image significantly influenced purchasing decisions. Partially, word of mouth and brand image had a more dominant influence than influencer marketing. These findings indicate that consumer reviews and brand perception play a significant role in driving purchasing decisions at Chat Cafe & Dimsum in Pontianak